1995
DOI: 10.1111/j.1365-2044.1995.tb05991.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nitrous oxide on propofol dosage and recovery after total intravenous anaesthesia for day‐case surgery

Abstract: SummaryWe studied the influence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Of these 12 studies, six did not include an intervention or comparator relevant to this review , in five studies the depth of anaesthesia differed between study arms [ and two papers reported on the ENIGMA‐2 study , which did not measure AAGA. Through this process we identified 22 publications covering 15 RCTs for inclusion in the review .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these 12 studies, six did not include an intervention or comparator relevant to this review , in five studies the depth of anaesthesia differed between study arms [ and two papers reported on the ENIGMA‐2 study , which did not measure AAGA. Through this process we identified 22 publications covering 15 RCTs for inclusion in the review .…”
Section: Resultsmentioning
confidence: 99%
“…One study , although included in the qualitative synthesis of this review, could not be included in the primary analysis as the number of participants in each group was not reported. Eleven studies included a single comparison of a study group with nitrous oxide and a group without nitrous oxide , whereas four studies included more than one comparison . These ‘multi‐arm’ studies, included four or three comparison groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Sukhani et al 30 examined eye opening and orientation in patients given general anesthesia that included propofol and nitrous oxide and found that there was a faster immediate recovery as compared with propofol alone. On the other hand, Lindekaer et al 31 showed that the addition of nitrous oxide to propofol-alfentanil anesthesia prolonged the early recovery period. In our study the recovery time required to return to an OAA/S score of 5 (R 1 ) was slightly longer in group N+P than in group P. However, because there was no difference in the time required to obtain a negative Romberg sign (R 2 ) between the groups, it is unlikely that nitrous oxide had a negative impact on recovery time.…”
Section: Discussionmentioning
confidence: 98%